Pengaruh Budaya Organisasi, Locus of Control dan Kepemimpinan terhadap Kepuasan Kerja Karyawan PT. BPR Guguk Mas Makmur Kabupaten Lima Puluh Kota - Thabrani, Gesit; Satar, Gustina (Jurnal Kajian Manajemen Bisnis, 2013)
This research was aimed at analyzing: (1) the effect of organizational culture on the work satisfaction, (2) the effect of Locus of Control on the work satisfaction, and (3) the effect of leadership on the work satisfaction. This research was conducted at PT. BPR Guguk Mas Makmur Kabupaten Lima Puluh kota. The population of the research was all employees working at PT. BPR Guguk Mas Makmur that consisted of 30 fellows. The sample was chosen by using total sampling technique. The data gotten from the sample was analyzed by usingÂ  descriptive and causative analyses assisted with SPSS version 15.00. The result of the research showed that; (1) organizational culture had a significant effect on the work satisfaction in which the level of significance was 0.048 (0.048<0.05), (2) Locus of Control did not affect the work satisfaction significantly in which the level of significance was 0.596 (0.596>0.05), and (3) leadership had a significant effect on the work satisfaction in which the level of significance was 0.001. Based on the result of the research, it was suggested to the company to concern on the employeeâ€™s condition that they can work well and purposeful. In addition, creating conducive work atmosphere and harmonic relationship among the employees in order to raise the employees work satisfaction should also be taken into account.